2004
DOI: 10.1242/dev.01364
|View full text |Cite
|
Sign up to set email alerts
|

The splanchnic mesodermal plate directs spleen and pancreatic laterality,and is regulated byBapx1/Nkx3.2

Abstract: The mechanism by which left-right (LR) information is interpreted by organ primordia during asymmetric morphogenesis is largely unknown. We show that spleen and pancreatic laterality is dependent on a specialised, columnar mesodermal-derived cell layer referred to here as the splanchnic mesodermal plate (SMP). At early embryonic stages, the SMP is bilateral, surrounding the midline-located stomach and dorsal pancreatic bud. Under control of the LR asymmetry pathway, the left SMP is maintained and grows lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
135
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(142 citation statements)
references
References 57 publications
5
135
2
Order By: Relevance
“…Apart from being important for interaction with underlying epithelium, the mesenchyme surrounding the dorsal pancreas also contributes to development of the spleen during early stages of development ( Fig. 1A; Kanzler and Dear 2001;Hecksher-Sorensen et al 2004).The mammalian homeobox gene Bapx1 (Nkx3.2) encodes a putative transcription factor that belongs to the Nkx gene family, most similar to the Drosophila homolog bap (Kim and Nirenberg 1989). Bapx1-null mutants show visceral mesoderm defects manifesting as asplenia and impaired pyloric sphincter formation (Lettice et al 1999;Tribioli and Lufkin 1999;Akazawa et al 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from being important for interaction with underlying epithelium, the mesenchyme surrounding the dorsal pancreas also contributes to development of the spleen during early stages of development ( Fig. 1A; Kanzler and Dear 2001;Hecksher-Sorensen et al 2004).The mammalian homeobox gene Bapx1 (Nkx3.2) encodes a putative transcription factor that belongs to the Nkx gene family, most similar to the Drosophila homolog bap (Kim and Nirenberg 1989). Bapx1-null mutants show visceral mesoderm defects manifesting as asplenia and impaired pyloric sphincter formation (Lettice et al 1999;Tribioli and Lufkin 1999;Akazawa et al 2000).…”
mentioning
confidence: 99%
“…Apart from being important for interaction with underlying epithelium, the mesenchyme surrounding the dorsal pancreas also contributes to development of the spleen during early stages of development ( Fig. 1A; Kanzler and Dear 2001;Hecksher-Sorensen et al 2004).…”
mentioning
confidence: 99%
“…1,4 By E13.5, the splenic primordium is visible as a ridge of cells on the dorsal stomach. A normally developing spleen can no longer be seen at this time in Hox11 À/À , capsulin À/À and Bapx1 À/À mice, [1][2][3]5 confirming the critical role of these transcription factors in spleen organogenesis. The first hematopoietic cells begin to appear in the spleen anlage, and between E13.5 and approximately E16.5, the spleen is a site of hematopoiesis in the fetus.…”
Section: Introductionmentioning
confidence: 94%
“…By E11.5, the expression of several transcription factors essential to spleen organogenesis including Hox11, Nkx2.5, capsulin/Pod-1, Wt1 and Bapx1 can be detected. [1][2][3] The molecular hierarchy regulating expression of these transcription factors, and the pathways they function within, are only beginning to be established. 1,4 By E13.5, the splenic primordium is visible as a ridge of cells on the dorsal stomach.…”
Section: Introductionmentioning
confidence: 99%
“…Both EFIC and OPT have been used to evaluate development in normal and mutant mouse embryos in several studies, and the reconstruction of complex 3D structures has revealed subtle changes in structure (Weninger and Mohun, 2002;Hecksher-Sorensen et al, 2004;Lickert et al, 2004;Meilhac et al, 2004;Rosenthal et al, 2004;Smyth et al, 2004;Wilkie et al, 2004;Takeuchi et al, 2005a;Weninger et al, 2005). The ability to collect 3D gene and protein expression data also makes it possible to create searchable atlases of expression data (Sarma et al, 2005), allowing for a greater appreciation of how changes in 3D morphology relate to changes at a molecular level.…”
Section: D Analysis Of Expression Patterns and Tissue Morphologymentioning
confidence: 99%